Tìm x:
\(3.5^{x-1}+6250=25^3\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Tìm xx biết: \left(x^{4}\right)^{3}=\dfrac{x^{19}}{x^{6}}(x4)3=x6x19
Trả lời: x=x=
a) 2(x-51) = 2^0.2^4 + 5.2^2
2(x-51) = 2^2(2^2+5)
2(x-51) = 36
x-51 = 18
x = 69
Vậy: x = 69
b) 225 : (x-19) = 25
x-19 = 9
x = 28
Vậy: x = 28
c) 4. (x-3)= 7^2-1^0
4. (x-3)= 48
x-3 = 12
x = 15
Vậy: x = 15
d) 3^3(x+4) - 3.5^2= 15.2^2
27 (x+4) - 75 = 60
27 (x+4) = 135
x+4 = 5
x = 1
Vậy: x = 1
e) 2x-7^2 = 5.3^2
2x - 49 = 45
2x = 94
x = 47
Vậy: x = 47
f) 2^3.5^2-(2x+6) = 4^3
200 - 2x - 6 = 64
194 - 2x = 64
2x = 130
x = 65
Vậy: x = 65
g) 135 - 5(x+4) = 35
5(x+4) = 100
x + 4 = 20
x = 16
Vậy: x = 16
h) 75 + 9(x-8) = 318
9(x-8) = 243
x-8 = 27
x = 35
Vậy: x = 35
Bài 1:
a: Ta có: 8,5<3,5x<15
mà x là số nguyên
nên \(3,5x\in\left\{10,5;14\right\}\)
hay \(x\in\left\{3;4\right\}\)
b: Ta có: \(\left(3-\dfrac{1}{3}x\right):2+1.5=3\)
=>(3-1/3x):2=1,5
=>3-1/3x=3
=>x=0
Bài 1: 25 + 3(x - 8) = 106
3(x - 8) = 106 - 25
3(x - 8) = 81
(x - 8) = 81 : 3
(x - 8) = 27
x = 27 + 8
x = 25
Bài 2: 720 : [41 - (2x - 5)] = 23 . 5
720 : [41 - (2x - 5)] = 8 . 5
720 : [41 - (2x - 5)] = 40
[41 - (2x - 5)] = 720 : 40
[41 - (2x - 5)] = 18
(2x - 5) = 41 - 18
(2x - 5) = 23
2x = 23 + 5
2x = 28
x = 28 : 2
x = 14
Bài 1:
a; (\(\dfrac{1}{4}\)\(x\) - \(\dfrac{1}{8}\)) x \(\dfrac{3}{4}\) = \(\dfrac{1}{4}\)
\(\dfrac{1}{4}x\) - \(\dfrac{1}{8}\) = \(\dfrac{1}{4}\) : \(\dfrac{3}{4}\)
\(\dfrac{1}{4}\)\(x\) - \(\dfrac{1}{8}\) = \(\dfrac{1}{4}\) x \(\dfrac{4}{3}\)
\(\dfrac{1}{4}x\) - \(\dfrac{1}{8}\) = \(\dfrac{1}{3}\)
\(\dfrac{1}{4}x\) = \(\dfrac{1}{3}\) + \(\dfrac{1}{8}\)
\(\dfrac{1}{4}\) \(x\)= \(\dfrac{8}{24}\) + \(\dfrac{11}{24}\)
\(\dfrac{1}{4}x=\dfrac{11}{24}\)
\(x=\dfrac{11}{24}:\dfrac{1}{4}\)
\(x=\dfrac{11}{24}\times4\)
\(x=\dfrac{11}{6}\)
b; \(\dfrac{12}{5}:x\) = \(\dfrac{14}{3}\) x \(\dfrac{4}{7}\)
\(\dfrac{12}{5}\) : \(x\) = \(\dfrac{8}{3}\)
\(x\) = \(\dfrac{12}{5}\) : \(\dfrac{8}{3}\)
\(x\) = \(\dfrac{12}{5}\) x \(\dfrac{3}{8}\)
\(x\) = \(\dfrac{9}{10}\)
Mình sửa đề luôn ^^
\(\frac{1}{3\cdot4}+\frac{1}{4\cdot5}+...+\frac{1}{x\left(x+1\right)}=\frac{3}{10}\)
\(\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+...+\frac{1}{x}-\frac{1}{x+1}=\frac{3}{10}\)
\(\frac{1}{3}-\frac{1}{x+1}=\frac{3}{10}\)
\(\frac{1}{x+1}=\frac{1}{30}\)
=> x + 1 = 30
=> x = 29
Vậy,..... @_@ ^^
\(3\cdot5^{x-1}+6250=25^3\)
=>\(\dfrac{3}{5}\cdot5^x=25^3-6250=9375\)
=>\(5^x=9375:\dfrac{3}{5}=15625\)
=>x=6